This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I ( n ) = ∫ 0 ∞ ( t − 1 ) n e − t d t
We know from the binomial expansion of ( t − 1 ) n that:
( t − 1 ) n = t n − ( n 1 ) t n − 1 + . . . . + ( n r ) t n − r ( − 1 ) r + . . . . ( n n ) ( − 1 ) n = r = 0 ∑ n ( n r ) t n − r ( − 1 ) r
Inputting this in the given integral and exchanging integral with summation:
I ( n ) = r = 0 ∑ n ( n r ) ( − 1 ) r ∫ 0 ∞ t n − r e − t d t
Now, invoking the gamma integral, we get:
I ( n ) = r = 0 ∑ n ( n r ) ( − 1 ) r ∫ 0 ∞ t n − r e − t d t I ( n ) = r = 0 ∑ n ( n r ) ( − 1 ) r ( n − r ) ! I ( n ) = r = 0 ∑ n r ! ( n − r ) ! n ! ( − 1 ) r ( n − r ) ! I ( n ) = n ! r = 0 ∑ n r ! ( − 1 ) r
This expression for I ( n ) is same as the number of derangements for n objects.
So,
I ( n ) = n ! r = 0 ∑ n r ! ( − 1 ) r = D ( n ) I ( n ) − D ( n ) = 0
Cheers! :)